Pemanfaatan Gadget dalam Mereduksi Perilaku Sosial terhadap Pola Komunikasi Peserta Didik di Sekolah Menengah Pertama - Nakhma’ussolikhah; Muslimah Muslimah; Shauma Nurul Fauzi; Ficky Adi Kurniawan (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
This research aims to identify the impact of gadget use on the social behavior and communication patterns of class VIII students at SMPN 1 Sumber. Based on the research results, it was found that the use of gadgets causes changes in students' social behavior, such as reduced cooperation, empathy and friendliness between students, as well as the emergence of selfish attitudes. This research used a qualitative approach with descriptive methods based on case studies, involving 6 respondents, namely 2 students, 2 parents, 1 guidance counselor and 1 homeroom teacher. Data collection was carried out through observation, interviews and documentation. Data analysis was carried out by collecting, reducing, presenting data and drawing conclusions, while data validity was obtained through triangulation. The research results show that excessive use of gadgets has an impact on abnormal behavior. Students tend to have anti-social attitudes and experience sleep disorders, and prefer to be alone. Apart from that, violent behavior and cyberbullying can also arise as a result of interactions in cyberspace. These impacts hinder students' social and emotional development, as well as affecting academic achievement at school. To overcome this negative impact, control is needed that involves schools and parents, such as limiting the time they use gadgets and encouraging them to be more active in social and extracurricular activities.